Changes in cervical isometric strength and anthropometry following a structured resistance training program in professional Rugby Union players - Appleby, B.; Williams, L.; Mist, S.; Naish, R.; Travers, M.; Higgins, C.; Konrath, J.; Fairchild, T. J. (Journal of Australian Strength and Conditioning, 2013)
The cervical region is frequently injured in collision sports such as rugby union. As a result, strength training programs for the cervical region have been implemented and these programs traditionally target the front row forward involved in the scrum. However, the tackle contest is often the primary cause of head and neck injury. Therefore, it is widely recommended that all players should partake in cervical strength training as a measure of injury prevention. While cervical muscle strength has previously been reported, the literature is limited in the adaptation of the cervical muscle group to specific resistance training in collision sport players. Furthermore, the relationship between cervical muscle strength and injury risk or injury severity in professional rugby union players is yet to be reported. Additionally, unpublished club injury data suggests a possible relationship between neck circumference, expressed as a robustness index (RI), and risk of neck injury. Therefore, the primary purpose of this investigation was to (i) determine the magnitude of strength adaptation following a specific cervical resistance training intervention; and (ii) to assess changes in neck circumference of players identified as being at-risk of injury to the cervical region. The secondary purpose was to identify whether an association between cervical strength and cervical injury statistics existed in a professional rugby union team.